Chemical Conversion of the Oil Palm Wastes - Lajis, Md Nordin; Sukari, Mohd Aspollah; Mohd Sharif, Atan; Hassan, Abdul Jalil (1988)
The production of a 2-furaldehyde (furfural) from mesocarp fibre waste and oil palm sludge from a palm oil mill using protic acids was investigated. The effect of immersion of fibre in acid prior to heating was also studied. Production of furfural was completed in 3-4 hours when hydrochloric (HCI) or sulfuric (H2S04 ) acids were used as the catalyst whereas a longer reaction time was required in the case of phosphoric (H3P04 ) or oxalic (H2C20 4 ) acids. The experiment showed that the rates of furfural production were increased when higher acid concentrations were applied. Immersion of fibre in the acids for 24 hours prior to reaction increased the furfural yield. The chemical conversion of sludge from the palm oil mill was also investigated. A similar acid concentration effect on the rate was observed.